Magnetic resonance neurography and diffusion tensor imaging of the peripheral nerves in patients with Charcot‐Marie‐Tooth Type 1A. Issue 6 (29th May 2017) - Vaeggemose, Michael; Vaeth, Signe; Pham, Mirko; Ringgaard, Steffen; Jensen, Uffe B.; Tankisi, Hatice; Ejskjaer, Niels; Heiland, Sabine; Andersen, Henning
ABSTRACT: Introduction: Investigation of peripheral neuropathies by magnetic resonance neurography (MRN) may provide increased diagnostic accuracy when performed in combination with diffusion tensor imaging (DTI). This study seeks to evaluate DTI in the detection of neuropathic abnormalities in Charcot‐Marie‐Tooth type 1A (CMT1A). Methods: MRI of the sciatic and tibial nerves, including MRN and DTI, was prospectively performed in 15 CMT1A patients and 30 healthy controls (HCs). The following MRI parameters were evaluated and correlated with clinical and neurophysiological findings: T2‐relaxation time, proton spin density (PD) and DTI (fractional anisotropy [FA] and apparent diffusion coefficient [ADC]). Results: DTI showed lower FA and higher ADC in CMT1A compared with HCs. T2 relaxation time showed no difference; however, PD of the sciatic nerve was higher in CMT1A. There were some close associations between neuropathy severity and MRN‐DTI, with the closest correlation between FA and nerve conduction velocity in the sciatic nerve ( r  = 0.76, P  < 0.01). Discussion: MRN‐DTI evaluation of sciatic and tibial nerves improves the detection of nerve abnormalities in patients with CMT1A. Muscle Nerve 56 : E78–E84, 2017